Reasons For Seeking Orthodontic Treatment A Pilot Study - Abdullah, A.A.A.; Yassin, Z.; Zamzam, N. (2001)
This pilot survey was conducted to determine the main reason and the motivating factors which, influence patients in seeking orthodontic treatment. 115 patients aged 11-30 years old were taken from the orthodontic waiting list at the Dental Faculty, University Malaya dated December 1999 - May 2000. A structured questionnaire was designed and the survey of patients was carried out using the telephone. The desire to have a better dental appearance was the main reason (65 %) given by patients who were seeking orthodontic treatment. The most important motivating factor that influences patients in seeking orthodontic treatment was to attain straight teeth (48 %). In conclusion, patients seek orthodontic treatment mainly due to psychological reason, which is to improve dental appearance and aesthetic. Perceived needs of an orthodontic patient should also be taken into consideration before commencing orthodontic treatment to increase chances of mutually satisfying result for both the orthoqontist and patient.